Improving Student Learning Outcomes Through the Application of Cooperative Script Models in Classroom Financial OTK Learning - Anah Tiranda (Pinisi Journal of Education and Management, 2022)
A learning process will definitely end with learning outcomes. Learning outcomes will never be produced if someone does not do something. This research is a classroom action research. The total number of students in class XI OTKP 1 odd semester for the academic year 2021/2022 is 27 people. Because of PTMT, students in one class must be divided into two groups/shifts. If it is divided into two shifts, there will be 14 in shift I and 13 people for shift II. And the subjects in this study were students in shift I as many as 14 people according to the cooperative script model setting students in pairs. This study uses 2 cycles and each cycle consists of 4 stages, namely: Planning, Implementation, Observation, and Reflection. Based on the results of the research, In the first cycle, learning management generally went well, but there were still things that needed to be improved, namely in time management and the need to increase student enthusiasm in participating in learning. However, in the second cycle of learning management has increased where all aspects are of good value and this has a positive impact on student learning mastery.